Morphological and anatomical characteristics and DNA barcode of Vanilla tiendatii - Mai, Yen Hoa; Phan-thi, Doan Trang; Truong, Duy Hoang; Trinh, Ngoc Nam; Tran-thi, Thu Trang; Nguyen-Phi, Nga; Van, Hong Thien (Journal of Phytology, 2024)
Vanilla tiendatii is a rare species and it has only been found in Quy Dat town, Minh Hoa district, Quang Binh Province, Vietnam. In this study, the detailed anatomical characteristics of this species were provided for the first time. Furthermore, five molecular markers, including ITS, psaB, psbB, psbC, and matK were firstly successfully sequenced. The lengths of these regions were ranging from 606 to 730 bps. They were deposited in the NCBI database with the accession numbers of PP696975, PP721190, PP721191, PP721189, and PP721188, respectively. The results also demonstrated that there were differences in these molecular markers between V. tiendatii and other Vanilla species, V. yersiniana and V. albida, which were similar in morphological characteristics.